Modelagem, simulação e análise do processo de produção do biodiesel brasileiro - Vendramin, Elton Joel (2010)
This work presents a simulation model for a biodiesel processing plant that fits the Brazilian case which utilizes soybean and cottonseed oils as major feedstocks. These pure oils or blends are modeled in this work according to a fatty acid expansion for each vegetable oil by considering abstract triglycerides with differentiated side chains. These components are characterized in the simulation by fundamental properties such as boiling point, molecular weight, density and critical temperature, pressure and volume. Some of them have reference values in the literature while others were estimated by Ambrose's group contribution method. In addition, two process flowcharts were modeled in steady state by using two different equipments for biodiesel downstream processing. In the first case, water washing and vacuum distillation columns are proposed. In the second case, there is a horizontal tank that represents a decantation unit followed by a vacuum distillation column. In both cases, reagents are fed to a continuous reactor where biodiesel plus glycerol conversion occurs. This conversion was modeled by using two different approaches. The first one considers a 95% fixed conversion while the second one uses kinetic data to describe the conversion as a function of reagents' concentration and temperature. The obtained results show the process efficiency for different feedstock compositions which are then used to accomplish a preliminary economic analysis. In addition, a process integration analysis is presented for the second process flowchart by using the pinch analysis. In this case, utility levels are calculated and a heat exchanger network is proposed.